Graphene Oxide Triggers Toll‐Like Receptors/Autophagy Responses In Vitro and Inhibits Tumor Growth In Vivo. Issue 9 (20th March 2014) - Chen, Guan‐Yu; Chen, Chiu‐Ling; Tuan, Hsing‐Yu; Yuan, Pei‐Xiang; Li, Kuei‐Chang; Yang, Hong‐Jie; Hu, Yu‐Chen
<x xml:space="preserve">Abstract</x> Graphene oxide (GO) is a nanomaterial with burgeoning bioapplications, while autophagy is implicated in cancer therapy. Although induction of autophagy by nanomaterials is reported, the underlying signaling mechanism in cancer cells and how this implicates the potential of GO in cancer therapy remain obscure. Here, it is shown that GO itself can induce the toll‐like receptors (TLRs) responses and autophagy in cancer cells and confer antitumor effects in mice. GO can be phagocytosed by CT26 colon cancer cells, simultaneously triggering autophagy as well as TLR‐4 and TLR‐9 signaling cascades. By dissecting the crosstalk between the TLRs and autophagy pathways, it is uncovered that the GO‐activated autophagy is regulated through the myeloid differentiation primary response gene 88 (MyD88)‐ and TNF receptor‐associated factor 6 (TRAF6)‐associated TLR‐4/9 signaling pathways. Injection of GO alone into immunocompetent mice bearing the CT26 colon tumors not only suppresses the tumor progression but also enhances cell death, autophagy, and immune responses within the tumor bed. These data altogether implicate the potential of GO as an effective nanomaterial for autophagy induction and cancer therapy.